Pengaruh Lingkungan Kerja Non Fisik, Stres Kerja Dan Kepuasan Kerja Terhadap Turnover Intention Karyawan Bagian Produksi Pada PT. Mustika Agung Sawit Gemilang Kab.Indragiri Hulu - Sri Bulandari; B. Isyandi; Machasin Machasin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The Effect of Non-Physical Work Environment, Job Stress and Job Satisfaction on Employee Turnover Intention in the Production Department at PT. Mustika Agung Sawit Gemilang Kab. Indragiri Hulu Under the guidance of Prof. Dr. B. Isyandi, SE, MS and Dr. Machasin, M.Sc.This study aims to determine and analyze the effect of Non-Physical Work Environment, Job Stress and Job Satisfaction on Employee Turnover Intention in the Production Department at PT. Mustika Agung Sawit Gemilang Kab. Indragiri Hulu. The method used in this research is quantitative. The types and sources of data in this study are primary data obtained from empirical research results through distributing questionnaires to employees who are sampled, the sample in this study is 120 people. The analysis technique used is the SPSS for windows program. The results of this study also show below: (1) Non-Physical Work Environment has a significant effect on Turnover Intention. (2) Job Stress has a significant effect on Turnover Intention. (3) Job Satisfaction has a significant effect on Turnover Intention. Keywords: Non-Physical Work Environment, Job Stress and Job Satisfaction on Employee Turnover Intention